POLITICAL CLASSES AND THEIR IMPACT ON THE SOCIAL ASPECT OF THE ALMOHAD STATE (668 AH - 1269 AD) - Ahmed Hill Sakheel Al- Anbari,; Hashim Nasser Hussein Al-Kaabi, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The issue of the social aspects of the Almohad state is one of the topics worthy of attention by specialists to study the social history of the Islamic Maghreb.In this search , we dealt with everything related to the social aspects of the Almohad state. The most important topics we discussed in this research were social groups, customs and social traditions. We also touched on the urban aspect ,and caring for women in Moroccan society, where women had an important and effective role in the Almohad society, and they contributed to the formation of society in the Almohad state, in addition to the presence of elements and groups of the Andalusian society and other dhimmis, Jews and Christians.